Analisa Minat Orang Tua Dalam Pemberian Vaksin MR Setelah Putusan MUI (Studi di Kecamatan Metro Pusat Tahun 2018) - Ita Dwilestari; Rakhmat Rakhmat (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
Vaccines or immunizations have become controversial. Various reasons are used by parents not to include their children when vaccines are carried out. One reason that is the basis is related to the content contained in the vaccine. Which makes the cause of the negative effects that occur due to the vaccine. In the city of Metro, especially in Metro Center Subdistrict, parents' interest in the MR Vaccine program prior to the MUI's decision was different. Many parents do not give MR vaccines for their children. In this study aims to explain the extent to which parents understand about MR vaccine. To analyze the interest of parents in the provision of MR Vaccines after the MUI's decision. This research is a type of field research. This research is descriptive qualitative, namely describing and describing the condition or an object then analyzing it. Sources of data in this study are the parents of children receiving MR Vaccines in Metro Pusat Subdistrict and also reference books that will complement the results of observations, interviews, and existing documentation. The results of this study are that parents' understanding of MR vaccines varies. There are parents who understand clearly there is also a lack of understanding. Whereas regarding the parents' interest in the MR Vaccine after the MUI's decision was that there were parents who stated that the decision had an effect, there were also parents who stated that the MUI's decision did not have a strong influence on its decision.